2015
DOI: 10.4236/ojapps.2015.58047
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Chemical Constituents of Bitumen Using a Mixed Solvent System

Abstract: Several solvents had been used to extract the SARA (Saturate, Aromatic, Resin and Asphaltene) constituents of bitumen. The quantification of such extracts also abounds in open literature but in this work an attempt was made to determine the quality of extraction as a feed stock for processing bitumen using a mixed solvent system. A mixture of heptane and toluene was used to compare with the standard method using heptane. The components were analysed for functional groups of compound types presented in them usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Supported by EDX data, showed that the present Carbon (C) element of Asbuton coated on TiO2/Ti NTAs. According to Odebunmi et al Asbuton extract contain C element such as saturated hydrocarbons, hydrogenated polycyclic aromatic compounds, and high molecular weight phenols and carboxylic acids [35]. EDX characterization ( Figure 5) shows the results of Asbuton-TiO2/Ti NTAs that were the presence of element content on the electrode surface.…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx)mentioning
confidence: 90%
“…Supported by EDX data, showed that the present Carbon (C) element of Asbuton coated on TiO2/Ti NTAs. According to Odebunmi et al Asbuton extract contain C element such as saturated hydrocarbons, hydrogenated polycyclic aromatic compounds, and high molecular weight phenols and carboxylic acids [35]. EDX characterization ( Figure 5) shows the results of Asbuton-TiO2/Ti NTAs that were the presence of element content on the electrode surface.…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx)mentioning
confidence: 90%
“…Hence, to achieve accurate quantification of naphtha, bitumen would likely need to be extracted from the tailings sample as well. For bitumen extraction, solvents should have a combination of paraffinic and aromatic components to extract all components of bitumen, including the asphaltenes which are generally insoluble in paraffins, but partially dissolve in aromatic solvents [32,35]. Grimaldos et al [36] reported higher diffusivity of bitumen into n-pentane compared to n-heptane or toluene due to its lower viscosity.…”
Section: Chemical Analysis Of Ftt Diluent 41 Diluent Extraction Techniquesmentioning
confidence: 99%
“…[4][5][6][7] To unlock this kind of unconventional oil ore, two other different methods have been proposed, including solvent extraction and pyrolysis. [8][9][10][11][12][13][14][15][16][17] Sui et al investigated the feasibility of solvent extraction in recovering asphalt from Indonesian asphalt rocks. They found that a high oil recovery (up to 98%) could be achieved with the solvent of toluene or cyclohexane.…”
Section: Introductionmentioning
confidence: 99%